Stepwise evolution of pandrug-resistance in Klebsiella pneumoniae - Zowawi, H.M.; Forde, B.M.; Alfaresi, M.; Alzarouni, A.; Farahat, Y.; Chong, T.M.; Yin, Wai Fong; Chan, Kok Gan; Li, J.; Schembri, M.A.; Beatson, S.A.; Paterson, D.L. (Nature Publishing Group, 2015)
Carbapenem resistant Enterobacteriaceae (CRE) pose an urgent risk to global human health. CRE that are non-susceptible to all commercially available antibiotics threaten to return us to the pre-antibiotic era. Using Single Molecule Real Time (SMRT) sequencing we determined the complete genome of a pandrug-resistant Klebsiella pneumoniae isolate, representing the first complete genome sequence of CRE resistant to all commercially available antibiotics. The precise location of acquired antibiotic resistance elements, including mobile elements carrying genes for the OXA-181 carbapenemase, were defined. Intriguingly, we identified three chromosomal copies of an ISEcp1-bla OXA-181 mobile element, one of which has disrupted the mgrB regulatory gene, accounting for resistance to colistin. Our findings provide the first description of pandrug-resistant CRE at the genomic level, and reveal the critical role of mobile resistance elements in accelerating the emergence of resistance to other last resort antibiotics.